Design, fabrication and sound absorption test of composite porous metamaterial with embedding I-plates into porous polyurethane sponge. (April 2021) - Gao, Nansha; Tang, Liling; Deng, Jie; Lu, Kuan; Hou, Hong; Chen, Kean
Abstract: Nowadays the use of porous polyurethane sponge (PPS) is very common for sound absorption, thanks to its light-weight feature and easy fabrication. However, in many circumstances the traditional PPS has very limited absorption capabilities, due to the slow wave phenomenon and/or to insufficient sub-wavelength sound absorption. In this paper, we propose a composite porous metamaterial (CPM) consisting in a porous polyurethane sponge with embedded multi-layer I-plates to mitigate this problem. To characterize the sound absorption coefficient of the proposed CPM, we resort to the Johnson-Champoux-Allard (JCA) model, where five acoustic parameters, namely porosity, flow resistivity, tortuosity, viscous, and thermal characteristic lengths, are determined by acoustic test methods. Numerical and experimental results show that the sound absorption performance of PPS in the CPM is remarkably improved, compared to a contrast structure and a pure porous material, taking advantage of a twofold mechanism of local acoustic energy dissipation of the I-plates and the slow wave phenomenon cancellation inside the structure. Finally, the effects of the geometrical parameters on average sound absorption coefficient are presented and discussed in detail. The scheme of this paper possesses potential application value for the design of broadband and efficient sound absorbers, providing a reference for researches of new acoustic functional devices with high absorption performances.